The Lawmaking Family - Noa Ben-Asher (Washington University Law Review, 2012)
Increasingly there are conflicts over families trying to “opt out” of various legal structures, especially public school education. Examples of opting-out conflicts include a father seeking to exempt his son from health education classes; a mother seeking to exempt her daughter from mandatory education about the perils of female sexuality; and a vegetarian student wishing to opt out of in-class frog dissection. The Article shows that, perhaps paradoxically, the right to direct the upbringing of children was more robust before it was constitutionalized by the Supreme Court in Meyer v. Nebraska (1923) and Pierce v. Society of Sisters (1925). In fact, the position of U.S. courts on opting-out conflicts has shifted dramatically over the twentieth century. In the early twentieth century, parents mostly prevailed in such conflicts. Today, the state typically prevails. Contemporary conflicts often involve public-school management of health, sexuality, and liberal development of students through surveys, nudges, and mandatory readings. When these techniques infringe on familial liberty, lawmakers lack conceptual tools to respond. A new understanding of familial liberty is needed. This Article offers that understanding. The approach here is based on the idea of family laws. Family laws are legal systems that families create or adopt to govern their day-to-day lives. These rules exist independently of state laws, and can be religious, such as Amish or Buddhist family laws, or secular, such as feminist or vegetarian family laws. The Article identifies three basic characteristics of family laws: They are (1) general and articulable; (2) grounded in religion, ethics, or morality; and (3) perceived as binding by members of a particular family. The Article argues that, with some limiting principles, lawmaking families should possess a liberty to opt out of programs and policies that conflict with a family law. Through an examination of three different types of family laws—religious, feminist, and vegetarian—the Article demonstrates how the proposed approach would empower existing lawmaking families. Almost a century has passed since the Supreme Court declared the liberty of parents to educate their children in Meyer v. Nebraska. It is time to breathe new life into this moribund liberty by empowering the Lawmaking Family.
Keywords: Meyer v. Nebraska; opt out; education; public schools; family laws